Strategy and Tactics of Soviet Security Bodies in the Fight Against Religion and Religious Communities on the Territory of Ukraine - Shakurova, Olha (Occasional papers on religion in Eastern Europe, 2023)
The article analyzes the strategy and tactics of state security agencies in the fight against religion and religious Protestant communities on the territory of Soviet Ukraine. It was revealed that the communist totalitarian system, in order to maintain its dominant position in society and master fully the consciousness of its population and influence its spiritual life (strategic task), shortly after the end of the Second World War, in 1946 in the system of the newly formed Ministry of State Security of the Soviet Union of the Socialist Republics and its republican departments created new special operational departments endowed with extraordinary powers to carry out punitive and repressive and complex preventive actions (tactical tasks). It was observed that the "O" (operational) department of the Ministry of State Security of the Ukrainian Soviet Socialist Republic was formed as a part of these functional divisions, which was engaged in the supervision of religious organizations, sects, groups, etc. It was found that the special department "O" of the Ministry of State Security - State Security Committee of the Ukrainian Soviet Socialist Republic was engaged in the planning and implementation of operational work on "agent and operational development of sectarians", and in its work relied on a number of punitive, repressive and preventive measures, which were discussed carefully at special meetings, the reports and minutes of which were classified, and only recently the "top secret" seal has been removed from them. It is substantiated that the execution of tasks related to the desacralization and liquidation of the prayer houses of the Evangelical Baptist Christians relied on operational commissioners and their agencies. It is shown that for the successful implementation of tasks related to the liquidation and termination of the prayer houses of Evangelical Baptist Christians, the special services of the State Security Committee combined skillfully punitive, repressive and preventive methods and systematically involved the cultural, educational and artistic intelligentsia of Soviet Ukraine.